2019
DOI: 10.1186/s12877-019-1370-1
|View full text |Cite
|
Sign up to set email alerts
|

Claims data-based analysis of the influence of individual and regional characteristics on the utilisation of long-term care by people with dementia in Baden-Wurttemberg, Germany

Abstract: BackgroundChallenges of future dementia care include increasing shortage of qualified healthcare providers and decreasing potential of informal care by relatives. In order to meet those challenges, changes in dementia care are needed. These changes should be based on data of both care utilisation and care supply. The aim of this study was to provide insight into individual and regional characteristics that influence the utilisation of long-term care by people with dementia.MethodsThe study was a retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Thirty-five studies (92%) were published after 2000 [ 9 , 34 , 35 , 37 , 38 , 40 48 , 50 , 51 , 53 62 , 64 73 ]. Twelve studies (32%) were from the United States of America [ 35 , 36 , 38 , 45 , 50 , 56 , 60 , 62 , 66 , 68 , 70 , 71 ], six studies (16%) were from Germany [ 43 , 47 , 57 , 58 , 67 , 72 , 73 ], five studies (13%) were from China [ 42 , 44 , 51 , 55 , 64 ], three studies were from Sweden [ 34 , 59 , 69 ], two studies were from each Ireland [ 48 , 54 ], Canada [ 40 , 53 ], Scotland [ 46 , 63 ], and South Korea [ 41 , 61 ]. Thus, 13 studies (34%) reported data from non-universal healthcare system [ 35 38 , 45 , 50 , 56 , 60 , 62 , 66 , 68 , 70 , 71 ], 12 studies (32%) reported data from universal government-funded healthcare system [ 9 , 34 , 39 , 40 , …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirty-five studies (92%) were published after 2000 [ 9 , 34 , 35 , 37 , 38 , 40 48 , 50 , 51 , 53 62 , 64 73 ]. Twelve studies (32%) were from the United States of America [ 35 , 36 , 38 , 45 , 50 , 56 , 60 , 62 , 66 , 68 , 70 , 71 ], six studies (16%) were from Germany [ 43 , 47 , 57 , 58 , 67 , 72 , 73 ], five studies (13%) were from China [ 42 , 44 , 51 , 55 , 64 ], three studies were from Sweden [ 34 , 59 , 69 ], two studies were from each Ireland [ 48 , 54 ], Canada [ 40 , 53 ], Scotland [ 46 , 63 ], and South Korea [ 41 , 61 ]. Thus, 13 studies (34%) reported data from non-universal healthcare system [ 35 38 , 45 , 50 , 56 , 60 , 62 , 66 , 68 , 70 , 71 ], 12 studies (32%) reported data from universal government-funded healthcare system [ 9 , 34 , 39 , 40 , …”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies were included in Patient-Centered Care [ 9 , 35 , 36 , 40 , 47 , 53 , 54 , 56 , 59 , 66 68 , 73 ]. Seven studies [ 36 , 40 , 47 , 56 , 59 , 67 , 68 ] reported on home care services and pointed toward lower use of these services in rural compared to urban PWD: while four studies [ 36 , 47 , 56 , 59 ] found that is true, the other three studies [ 40 , 67 , 68 ] found higher use in rural PWD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations